The impact of the COVID-19 pandemic on the global tuberculosis epidemic - Falzon, Dennis; Zignol, Matteo; Bastard, Mathieu; Floyd, Katherine; Kasaeva, Tereza (Frontiers in Immunology, 2023)
Tuberculosis (TB) is a major cause of ill health worldwide. Until the coronavirus (COVID-19) pandemic, TB was the leading cause of death from a single infectious agent. COVID-19 has caused enormous health, social and economic upheavals since 2020, impairing access to essential TB services. In marked contrast to the steady global increase in TB detection between 2017 and 2019, TB notifications dropped substantially in 2020 compared with 2019 (-18%), with only a partial recovery in 2021. Background TB epidemiology worsened during the pandemic: the estimated 10.6 million people who fell ill with TB worldwide in 2021 is an increase of 4.5% from the previous year, reversing many years of slow decline. The annual number of TB deaths worldwide fell steadily between 2005 and 2019, reaching 1.4 million in 2019, but this trend was reversed in 2020 (1.5 million), and by 2021 global TB deaths were back to the level of 2017 (1.6 million). Intensified efforts backed by increased funding are urgently required to reverse the negative impacts of COVID-19 on TB worldwide, made more pressing by ongoing conflicts, a global energy crisis and uncertainties in food security that are likely to worsen the broader determinants of TB.